CAN THYROID DYSFUNCTION INDUCE PERIODONTAL DISEASE? - Adriana Monea; Nagy Elod; Alexandru Sitaru; Alexandra Stoica; Monica Monea (European Scientific Journal, ESJ, 2014)
Objective: to determine if thyroid dysfunction can induce periodontal disease, by comparing salivary and serum levels of IL-6 and TNF-α in patients with thyroid dysfunction without clinical periodontal changes to healthy controls. Material and Methods: 28 randomly selected adult patients with thyroid dysfunction and 24 healthy adults were enrolled. Venous blood and unstimulated saliva were assessed for TNF-α and Interleukin-6 levels, using ELISA-sandwich methods. Comparisons between groups were made using Mann-Whitney and Kruskal-Wallis tests, and the level of significance was set at p≤0.05. Results: Mean values of serum TNF-α concentration for patients with hypothyroidism (132.29±91.26pg/ml) were 4 times higher than in subjects with hyperthyroidism (32.24±29.46pg/ml) and almost 15 times higher than in controls, but there was no significant difference between hypo- and hyperthyroid subjects. Mean values of salivary TNF-α were significantly higher in hyperthyroid subjects than in controls (p=0.011), also in hypothyroid subjects than in controls (p=0.009), but there was no significant difference between hypo- and hyperthyroid subjects. Serum IL-6 had apparently much higher levels in study groups (99.39±54.41pg/ml hyperthyroid and 68.69±45.94pg/ml in hypothyroid) compared with controls (11.23±2.14pg/ml), but the differences were not statistically significant. Mean values of salivary IL-6 were significantly higher both in hyperthyroid and hypothyroid subjects than in controls (p<0.001), and there was an extremely significant difference between hypo- and hyperthyroid subjects (p<0.001). Conclusion: Serum and salivary levels of TNF-α and IL-6 represent a well individualized biologic indicator for appreciating the development of periodontitis in subjects with thyroid dysfunction. Hyperthyroidism can induced more important periodontal destructions than hypothyroidism.